Humoral immune activation in amyotrophic lateral sclerosis patients - Michael Rentzos; Maria Elepthera Evangelopoulos; Eleni Sereti; Vassiliki Zouvelou; Styliani Marmara; Theodoros Alexakis; Ioannis Evdokimidis (MDPI AG, 2013)
There is evidence that immunological factors may involved in the pathogenetic mecha- nisms of amyotrophic lateral sclerosis (ALS). Few studies to date have explored the status of the humoral immune response in patients with ALS. We examined the presence of humoral immune activation in ALS patients, serum immunoglobulins (IgG, IgA and IgM) levels were measured in 36 patients with ALS and 35 normal controls. Serum IgG, IgM and IgA levels were not significantly different in our ALS patients compared with the control group (P=ns). No correlations of serum IgG, IgM and IgA concentrations with duration, severity of the disease or the clinical form of onset (bulbar or spinal) were found in our ALS patients. Our results do not suggest a humoral immune activation in ALS patients. This does not exclude that immunological mechanisms may be involved in ALS pathogenesis.